Surgical Management of Spinal Metastases: Balancing Oncologic Control and Neurological Function - Muhammad Zahid Khan, Abdul Satar, Samir Khan Kabir, Muhammad Saeed, Muhammad Waqar, Mazhar Chaudary, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the outcomes of traditional and minimally invasive surgery in the treatment of spinal metastases, focusing on pain relief, neurological function, and oncological control. Methodology: A retrospective analysis was conducted on 150 patients who underwent surgery for spinal metastases at Hayatabad Medical Complex between January 2015 and January 2022. Of these, 100 patients received traditional surgery, while 50 underwent minimally invasive surgery. Data on pain relief (measured using the Visual Analog Scale), neurological function (using the ASIA scale), and oncological control were collected and analysed. Statistical tests, including independent t-tests and chi-square tests, were used to assess differences between the two groups. Results: Minimally invasive surgery provided significantly better pain relief (mean VAS score = 3.8) compared to traditional surgery (mean VAS score = 5.2) with a p-value of 0.03. Neurological outcomes were also superior in the minimally invasive group, with 70% of patients reporting improved or stable function compared to 55% in the traditional surgery group. Oncological control was similar in both groups, with stable or reduced tumor size in 60% of traditional surgery patients and 70% of minimally invasive surgery patients. Conclusion: Minimally invasive surgery offers superior pain relief and neurological outcomes compared to traditional surgery for spinal metastases, while providing similar oncological control. The results suggest that minimally invasive surgery is a promising alternative for managing spinal metastases, particularly in improving patient quality of life. Keywords: spinal metastases, minimally invasive surgery, traditional surgery, pain relief, neurological function